A Versatile Industrial Timer and Real Time Keeper - Yadav, Sagar. G; Narayanankutty, K. A (Scientific Research Publishing, 2011)
Industrial timer requirements are multifaceted. On-delay, off-delay, cyclic or sequential timing requirements, with usual time range varying from seconds to days, depending on the process. Custom build timers cannot provide all of these requirements simultaneously and hence an advanced timer rectifying this shortcoming has been designed and fabricated in this work. This timer is based on the real time clock chip used in mother boards. Our design can be programmed for a specific time requirement and can later be put to work in standalone mode. A demonstration board is fabricated and tested.
Keywords: Industrial Timer; Real Time Clock; Programmable; Standalone; DS1307; I2C; USART; ZigBee; Bluetooth